2016
DOI: 10.1017/s0033291716000684
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness and surface area correlates with cognitive dysfunction among first-episode psychosis patients

Abstract: Significant correlations between CTh and CA with neurocognitive performance were localized in brain areas known to be involved in cognition. The results also suggested a disrupted structure-function relationship in FEP patients compared with CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 74 publications
2
8
0
Order By: Relevance
“…Contrary to these results, others studies showed reduced cortical thickness in frontal regions in first-episode schizophrenia patients [31,32]. It is important to mention that cortical thickness has been related to cognitive dysfunction in FEP patients [33].…”
Section: Discussionmentioning
confidence: 76%
“…Contrary to these results, others studies showed reduced cortical thickness in frontal regions in first-episode schizophrenia patients [31,32]. It is important to mention that cortical thickness has been related to cognitive dysfunction in FEP patients [33].…”
Section: Discussionmentioning
confidence: 76%
“…Correlations between general cognitive ability and GMV and CT were positive and consistent with studies of healthy individuals (25, 27, 36), whereas correlations between general cognitive ability and CSA were negative. Studies correlating CSA and cognition yield inconsistent results, with some showing positive correlations (25, 36, 70) and others showing negative (71) or no correlations between the two measures in healthy samples (72). The use of ICV as an adjustment variable may contribute to the negative relationship between general cognitive ability and CSA.…”
Section: Discussionmentioning
confidence: 99%
“…In FEP, volumetric decreases in thalamus, insula, and anterior cingulate have been consistently identified 38 . In addition, cortical thickness reductions have been reported, particularly across frontal regions [39][40][41][42][43][44] although some studies have also identified thinning in parietal and temporal regions including fusiform gyrus 39,42 . Regarding cortical thinning, the studies that have investigated this in FEP point to a fairly consistent pattern of thinning across frontal and parietal cortices 44 sometimes accompanied by thinning in temporal regions 42,45 .…”
Section: Brain Structural Correlates Of Functional Capacity In First-mentioning
confidence: 99%